Environmental governance in the context of desertification combate on Paraíba state (Research, Society and Development, 2020)
This study aimed to analyze how environmental governance it’s inserted in the policy to combat desertification of Paraíba state instituted by PAE-PB and its relationship with the concept of good governance. This is an exploratory, documentary research, with a quantitative and qualitative approach, carried out between August 2019 and June 2020. It was identified, from the speeches on public participation and on decentralization, that environmental governance is inserted implicitly in the PAE-PB and that the principles of public participation, inclusiveness, rule of law, effectiveness, efficiency, transparency and accountability, they are disseminated among premises, actions, objectives and institutional structure, in differing statistical proportions and approaches. It was found that there is a predominance of public participation and inclusiveness, indicating the need for changes in the rhetoric used in the plan, with a view to making evident the need for the implementation of the other principles when it is carried out. Thus, in light of aspects that make up the political and social scenario of the semi-arid region of Paraiba, considerations was made, aiming to bring environmental governance in PAE-PB closer to the concept of good environmental governance.